Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms22158264
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Spiro-Fused [3-azabicyclo[3.1.0]hexane]oxindoles as Potential Antitumor Agents: Initial In Vitro Evaluation of Anti-Proliferative Effect and Actin Cytoskeleton Transformation in 3T3 and 3T3-SV40 Fibroblast

Abstract: Novel heterocyclic compounds containing 3-spiro[3-azabicyclo[3.1.0]hexane]oxindole framework (4a, 4b and 4c) have been studied as potential antitumor agents. The in silico ADMET (adsorption, distribution, metabolism, excretion and toxicity) analysis was performed on 4a–c compounds with promising antiproliferative activity, previously synthetized and screened against human erythroleukemic cell line K562 tumor cell line. Cytotoxicity of 4a–c against murine fibroblast 3T3 and SV-40 transformed murine fibroblast 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…The results of these investigations are presented in Figure 2. Based on our previous studies, [20][21][22]24,29 we selected phenyl (4a), carboxymethyl (4e) and N-isopropylcarbamoyl (4f) substituted cyclopropa[a]pyrrolizines along with spirobarbiturate-3-azabicyclo[3.1.0]hexanes containing either a methyl (6b, 6j) or an isobutyl (6g, 6o, 6t) substituent for this preliminary study. Phenyl-substituted cyclopropane ring cycloadducts were found to be more active in both cases (compare 4a vs. 4e or 4f and 6b or 6g vs. 6j, 6o or 6t).…”
Section: Biological Assaymentioning
confidence: 99%
“…The results of these investigations are presented in Figure 2. Based on our previous studies, [20][21][22]24,29 we selected phenyl (4a), carboxymethyl (4e) and N-isopropylcarbamoyl (4f) substituted cyclopropa[a]pyrrolizines along with spirobarbiturate-3-azabicyclo[3.1.0]hexanes containing either a methyl (6b, 6j) or an isobutyl (6g, 6o, 6t) substituent for this preliminary study. Phenyl-substituted cyclopropane ring cycloadducts were found to be more active in both cases (compare 4a vs. 4e or 4f and 6b or 6g vs. 6j, 6o or 6t).…”
Section: Biological Assaymentioning
confidence: 99%
“…We used derivatives of isatin [ 22 ], alloxan [ 23 ], ninhydrin [ 24 , 25 , 26 , 27 ], 11 H -indeno[1,2- b ]quinoxalin-11-one [ 28 ], and tryptanthrin [ 29 ] as the ketone components. The products of these reactions were pharmacologically interesting spiro-fused 3-azabicyclo[3.1.0]hexanes and pyrrolizines, some of which were identified as exhibiting in vitro antitumor activity [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our recent works it was shown that (spiro) azabicyclo[3.1.0]hexanes and (spiro) cyclopropa[ a ]pyrrolizines are readily available from cyclopropenes and azomethine ylides (generated in situ from amino acids or peptides and carbonyl compounds such as ninhydrins, indenoquinoxalines, pyrroloisoquinolines and tryptanthrines) and some adducts inhibited the cancer cells grows in vitro [ 33 , 34 , 35 , 36 , 37 ]. In addition, the morphological changes of cells occurring under the action of these compounds (in particular, such cytoskeleton components as actin microfilaments) suggest that the studied substances have not only cytostatic activity, but also can lead to a decrease in metastasis of tumor cells, which opens up broad prospects for the study of their action in vivo [ 38 ].…”
Section: Introductionmentioning
confidence: 99%